2019
DOI: 10.3390/ijerph17010131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Nicotine Fact Sheet on Perceived Risk of Nicotine and E-Cigarettes and Intentions to Seek Information About and Use E-Cigarettes

Abstract: We examined how a nicotine fact sheet influenced smokers’ beliefs about nicotine and electronic cigarettes (e-cigarettes), a potentially less harmful alternative to conventional cigarettes. In an exploratory online experiment, 756 US adult current and recent former smokers (quit in the past 2 years) were randomized to view a nicotine fact sheet or control messages (bottled water ads). Effects of the nicotine fact sheet on perceived nicotine addictiveness, nicotine risk, comparative risk of e-cigarettes, and du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Information and education should be provided particularly to young consumers in their 20s, who have low risk perception about chemical products. Providing consumer education should be considered because consumers' risk perception affects public health and personal risk management [30][31][32][33][34]; along with expert opinions, the public's risk perception is an essential element in improving public health and the policy-making process [35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Information and education should be provided particularly to young consumers in their 20s, who have low risk perception about chemical products. Providing consumer education should be considered because consumers' risk perception affects public health and personal risk management [30][31][32][33][34]; along with expert opinions, the public's risk perception is an essential element in improving public health and the policy-making process [35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…[30] conducted a comprehensive risk assessment analysis associated with establishing a prompt alarm system to prevent or restrict the sale and use of products (e.g., tainted or harmful toys, cosmetics, and chemicals) that pose a serious risk to consumer health and safety. In addition, many studies conducted surveys on consumers' risk perceptions and attitudes toward hazardous products [31][32][33][34]. Those studies found that consumers' risk perception of hazardous products affected their individual risk management in terms of the environment and health as well as their attitude.…”
Section: Introductionmentioning
confidence: 99%
“…This study is part of a larger experiment on e-cigarette and nicotine risk communication. Specifically, the whole experiment included five message conditions ( n = 1906; for a detailed description of the five conditions, see our earlier publications [ 50 , 51 ]). In the current study, we analyzed data from only two of the five message conditions relevant to our hypotheses ( n = 761; discussed below).…”
Section: Methodsmentioning
confidence: 99%
“…Risk information, such as warnings or guidelines, appear in the form of labels, instructions, and/or pictograms on CHP containers to raise awareness of hazards; they also provide guidance for implementing suitable risk management behaviors [2,13]. This information can help individuals make better "informed" risk-management decisions [14]. Certain regulations require product risk information to be written or printed clearly on the product package or container, and an understanding of risk information messages by users is a fundamental pillar of chemical legislation [15].…”
Section: Introductionmentioning
confidence: 99%